Lipid Membrane‐Based Antigen Presentation to B Cells Using a Fully Synthetic Ex Vivo Germinal Center Model. Issue 7 (28th April 2022) - Kramer, Liana; Song, Hannah W.; Mitchell, Kaiya; Kartik, Mythili; Jain, Ritika; Escarra, Victoria Lozano; Quiros, Enrique; Fu, Harrison; Singh, Ankur; Roy, Krishnendu
Abstract : High‐affinity antigen‐specific B cells are generated within specialized structures, germinal centers (GCs), inside lymphoid organs. In GCs, follicular dendritic cells (FDCs) present antigens on their membrane surface to cognate B cells, inducing rapid proliferation and differentiation of the B cells toward antibody‐secreting cells. The FDC's fluid membrane surface allows B cells to "pull" the antigens into clusters and internalize them, a process that frequently involves tearing off and internalizing FDC membrane fragments. To study this process ex vivo, liposomal membranes are used as the antigen‐presenting FDC‐like fluid lipid surface to activate B cells. In a fully synthetic in vitro GC model (sGC), which uses the microbead‐based presentation of the CD40 Ligand and a cytokine cocktail to mimic T follicular helper cell signals to B cells, liposomes presenting a model antigen mimic effectively engage B cell receptors (BCRs) and induce greater BCR clustering compared to soluble antigens, resulting in rapid antigen internalization and proliferation of the B cells. B cells showed GC‐like reactions and undergo efficient IgG1 class‐switching. Taken together, the results suggest that fluid membrane‐bound antigen induces a strong GC response and provides a novel synthetic in vitro system for studying GC biology in health and diseases, and for expanding therapeutic B cells ex vivo. Abstract : B cell generation in the germinal center (GC) involves membrane‐bound antigen presentation on the surface of follicular dendritic cells (FDCs). The B cells internalize the antigen, often tearing off and internalizing FDC membrane fragments as well. Herein, antigen‐presenting liposomal membranes are designed to mimic the FDC fluid lipid surface in an ex vivo GC culture system, resulting in a strong GC response.